USE OF Xpert MTB/RIF IN MOLECULAR DIAGNOSTICS OF PLEURAL TB EMPYEMA - Koshak, Yu. F. (Medical Informatics and Engineering, 2020)
Background. The first of effective analysis of the test diagnosis of patients with pleural TB empyema from the use of Xpert MTB/RIF examination in Videothoroscopic (VTS) studies of the chest organs is presented. Materials and methods. Results. The thoroscopic features of developpment, localization in diagnostics of pleural TB are analyzed into depending on the sex, age, beginning, course and prevalence of suppuration. The feature of Xpert MTB/ RIF Express in early diagnosis of TB empyema pleura and Minimally invasive surgical treatment (VTS, VATS) of patients is shown. Conclusions. In patients with tuberculosis empyema of the pleura, only 51.2 % of pleural empyema was diagnosed in a timely manner, that is, at the stage of a possible minimally invasive surgical treatment. Analysis of the diagnostic value of standard methods for the diagnosis of tuberculosis suppuration in patients with tuberculosis showed that the timely detection of such a complication is significant difficulty. In 48.7 % of patients, tuberculosis empyema was diagnosed at a late stage of the purulent process, which confirms the need for widespread use in the diagnosis of Xpert MTB/RIF testing, which provides higher sensitivity than microscopy.